Size‐Independent Transmembrane Transporting of Single Tetrahedral DNA Nanostructures. Issue 3 (20th November 2019) - Chen, Xi; Tian, Falin; Li, Min; Xu, Haijiao; Cai, Mingjun; Li, Qian; Zuo, Xiaolei; Wang, Hongda; Shi, Xinghua; Fan, Chunhai; Baigude, Huricha; Shan, Yuping
Abstract: DNA nanostructures have attracted considerable attention as drug delivery carriers. However, the transmembrane kinetics of DNA nanostructures remains less explored. Herein, the dynamic process of transporting single tetrahedral DNA nanostructures (TDNs) is monitored in real time using a force‐tracing technique based on atomic force microscopy. The results show that transporting single TDNs into living HeLa cells need ≈53 pN force and ≈25 ms duration with the average speed of ≈0.6 µm s −1 . Interestingly, the dynamic parameters are irrelevant to the size of TDNs, while the larger TDNs rotated slightly during the transporting process. Meanwhile, both the results from single‐molecule force tracing and ensemble fluorescence imaging demonstrate that the different size TDNs transmembrane transporting depends on caveolin‐mediated endocytosis. Abstract : DNA nanostructures with inherent biocompatibility have become a unique vehicle in drug delivery. The transmembrane process is the first and the most important step for drug delivery. Herein, the transporting of single tetrahedral DNA nanostructures (TDNs) is recorded by a force‐tracing technique based on atomic force microscopy, and the size effect of TDNs on the transporting dynamics is studied.